(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
In modern conditions, the problem of professional orientation of high school students is relevant and is in the focus of attention of researchers. A young person, as a future specialist, tries to find his place among the professions, passing a long path of acquiring knowledge. Meanwhile, the large flow of information often makes it difficult for a high school student to independently orient himself in the matter of choosing a profession. In this matter, both the family (parents) and the school (specialist, social pedagogue) play an important role, whose effective guidance and support will not only help the child in choosing a profession, but will also ensure the economic, social, scientific development of society.